Subtitling Tarantino’s offensive and taboo dialogue exchanges into european spanish: the case of Pulp Fiction - José Javier Ávila-Cabrera (Revista de Lingüística y Lenguas Aplicadas)
The manner offensive and taboo language is subtitled becomes a delicate and controversial practice given that this type of language functions as a lexical vehicle that provides information on the characters’ personality, social class, and setting and can provoke a strong reaction on viewers (Díaz Cintas, 2001). The omission of offensive/taboo words can therefore be said to entail a loss in their communicative function. From a Descriptive Translation Studies approach, the goals of this paper attempt to shed some light on the way the film Pulp Fiction (Quentin Tarantino, 1994) was subtitled into European Spanish by delving into diverse matters such as: (1) the translation strategies utilised by the subtitler; (2) the way offensive/taboo dialogue exchanges were transferred on the screen; and (3) proving whether the cases of neutralisation and omission of the load of these terms might have been justified by the technical constraints of subtitling.